Electrode for synthesizing RT base as well as preparation method and application of electrode
By loading copper and lanthanum active components on the electrodes, RT PES was synthesized by electrochemical reactions, and the problem of poor catalyst activity and durability in the prior art was solved, and efficient and low-cost RT PES synthesis was achieved.
Patent Information
- Application Number
- CN202411994752.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has poor catalytic activity and durability of catalysts when preparing RT PES, and poor selectivity, and high cost of precious metal catalysts, which are prone to residues in the product, affecting performance.
An electrode for the synthesis of RT PES is provided, the electrode includes a matrix and an active component supported on the surface of one side of the matrix, and the active components include copper and lanthanum. It is directly used for the synthesis of RT PESES through electrochemical reactions, avoiding the use of noble metal catalysts.
It realizes efficient RT PES synthesis, the electrode has high catalytic activity and durability, reduces power consumption, improves raw material conversion rate and product selectivity, and is suitable for large-scale production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to an electrode for synthesizing RT base, a preparation method and an application thereof. Background Art
[0002] Rubber antioxidants are mainly divided into p-phenylenediamine, quinoline, naphthylamine, phenol, etc. according to their structure. P-phenylenediamine and quinoline antioxidants are mainly suitable for tires, especially radial tires, and p-phenylenediamine antioxidants are widely used due to their best protective performance. The main varieties of p-phenylenediamine rubber antioxidants are 4010NA, 4020, etc., and their key intermediates are p-aminodiphenylamine (PADPA), also known as N-phenyl p-phenylenediamine and 4-aminodiphenylamine. 4-Aminodiphenylamine, commonly known as RT-base, is an important organic chemical intermediate, mainly used in the production of p-phenylenediamine rubber antioxidants such as 4020, 4010NA, 4010, 688, etc. In addition, RT-base is also used to synthesize dyes such as blue salt VRT, acid red GR, and disperse yellow GFL. It is widely used in industrial fields such as rubber additives, dyes, textiles, and printing.
[0003] There are more than 10 synthetic processes for RT base. The current industrial production methods mainly include the aniline method, diphenylamine method, formanilide method and nitrobenzene method. The nitrobenzene method is an improvement on the formanilide method. It uses nitrobenzene and aniline as raw materials to generate 4-nitrosodiphenylamine and 4-nitrodiphenylamine under the action of a catalyst. The resulting mixture is hydrogenated and reduced under the action of a precious metal catalyst to obtain RT base. In recent years, the liquid phase catalytic hydrogenation method for the continuous preparation of RT base has been successfully developed. It is a similar process to the nitrobenzene method, and the entire production process achieves fully closed continuous production; however, this method requires the use of precious metal catalysts during reduction, which is costly, and the product is prone to residues, affecting product performance; and the reduction process requires the use of a large amount of hydrogen, which poses great challenges. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the difficulties of the prior art in which the RT base catalyst prepared by the electrochemical method has poor catalytic activity and durability, as well as the prior art in which the catalyst selectivity is poor when preparing RT base, thereby providing an electrode for synthesizing RT base and a preparation method and application thereof.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The invention provides an electrode for synthesizing RT base, comprising a substrate and an active component loaded on a surface of one side of the substrate, wherein the active component comprises copper and lanthanum.
[0007] It should be noted that the active components copper and lanthanum exist in the electrode in the form of elemental copper and elemental lanthanum.
[0008] Furthermore, the mass ratio of copper to lanthanum is (50-100):1.
[0009] Further, the substrate comprises an ion exchange membrane; preferably, the ion exchange membrane comprises a perfluorosulfonic acid ion exchange membrane; and / or,
[0010] The surface of the substrate on the side opposite to the active component is loaded with an anode active material; and / or,
[0011] The loading amount of the active component in the matrix is 5-10 mg / cm 2 and / or,
[0012] The size of the electrode is 1×1 cm 2 ~100×100cm 2 ; Preferably, the size of the electrode is 20×20cm 2 ~50×50cm 2 .
[0013] The ion exchange membrane has electrical conductivity and ion conductivity, and copper lanthanum active components and platinum nanoparticles are coated on both sides of the ion exchange membrane, wherein the side of the ion exchange membrane containing the copper lanthanum active components is the cathode side, and the side containing the platinum nanoparticles is the anode side, and the electrode can be directly used for electrochemical reduction of 4-nitrodiphenylamine to synthesize RT base. The anode active material of the present invention is an electrochemical anode material known in the art, such as platinum nanoparticles and other substances. Among them, the platinum nanoparticles can be coated on one side of the substrate with reference to the existing technology in the art, for example, a LUXORPt brand nano platinum spraying instrument is used to automatically sputter platinum particles to form a coating with a thickness of 1 to 100 nm.
[0014] The present invention provides a method for preparing an electrode for synthesizing RT base, comprising:
[0015] (1) preparing a copper-containing suspension;
[0016] (2) adding a lanthanum source to the copper-containing suspension to prepare a slurry containing copper and lanthanum;
[0017] (3) The slurry is coated on one surface of the substrate and sintered.
[0018] Furthermore, in step (1), the copper salt is made into a copper salt solution; a reducing agent is added to the copper salt solution to react and prepare the copper-containing suspension;
[0019] Preferably, the copper salt includes at least one of a monovalent copper salt and a divalent copper salt; the copper salt is a sulfate, a carbonate, a chloride, a nitrate, and the like.
[0020] Preferably, the molar ratio of the copper salt to the reducing agent is 1:(0.5-4);
[0021] Preferably, the reaction temperature is 120-240°C and the reaction time is 3-8h;
[0022] Preferably, the copper-containing suspension is a nano-copper suspension; the copper in the copper-containing suspension is nano-scale, which can increase the specific surface area and improve the catalytic activity of copper.
[0023] Preferably, the reducing agent comprises at least one of lithium aluminum hydride and alkali metal borohydride;
[0024] Preferably, the alkali metal borohydride comprises at least one of sodium borohydride and potassium borohydride;
[0025] Preferably, before carrying out the reaction, the method further comprises the step of adding an alcohol organic substance;
[0026] Preferably, the alcohol organic compound contains at least 2 hydroxyl groups;
[0027] Preferably, the alcohol organic matter includes at least one of an alcohol polymer and an alcohol compound;
[0028] Preferably, the number of carbon atoms in the alcohol compound is 2 to 7;
[0029] Preferably, the alcohol polymer comprises polyethylene glycol;
[0030] Preferably, the alcohol compound includes at least one of diethylene glycol and glycerol.
[0031] The present invention has no requirement on the amount of alcohol organic matter used, because the alcohol organic matter will be removed after sintering, so the amount of alcohol organic matter added during the preparation of the slurry is selected according to needs.
[0032] Further, in step (2), the lanthanum source includes at least one of lanthanum fluoride, lanthanum oxide, lanthanum nitride, lanthanum carbide, lanthanum phosphide, lanthanum nitrate, lanthanum phosphate, lanthanum carbonate and lanthanum sulfate;
[0033] Preferably, the slurry further comprises perfluorosulfonic acid resin; when preparing the slurry, the perfluorosulfonic acid resin is added in the form of a solution or suspension, i.e., a Nafion solution, such as a suspension solution of perfluorosulfonic acid resins of the Nafion 117 series in isopropanol, water, etc. The Nafion solution can act as an adhesive to bond the copper particles to the surface of the ion exchange membrane, and after sintering, the Nafion solution can also form a part of the ion exchange membrane.
[0034] Preferably, the mass ratio of the copper element in the copper salt to the perfluorosulfonic acid resin is 100:(5-10);
[0035] Preferably, the slurry further comprises a pore former;
[0036] Preferably, the mass ratio of the copper element in the copper salt to the pore-forming agent is 100:(5-10);
[0037] Preferably, the pore-forming agent comprises at least one of acrylic cross-linked resin and cellulose and its derivatives;
[0038] Preferably, the acrylic acid cross-linked resin comprises carbomer;
[0039] Preferably, the cellulose includes at least one of carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, ethyl cellulose and hydroxyethyl methyl cellulose.
[0040] Furthermore, in step (3), the coating is performed by spraying;
[0041] Preferably, the spraying parameters include: a temperature of 160 to 180° C.; and / or a spraying speed of 0.1 to 1 m / s; and / or a spraying distance of 0.1 to 1 cm;
[0042] Preferably, the spraying is carried out under a protective atmosphere;
[0043] Preferably, the sintering temperature is 350-400°C;
[0044] Preferably, the sintering is performed under a protective atmosphere.
[0045] When preparing the electrode, the slurry coating and sintering are both carried out under a protective atmosphere, such as nitrogen or an inert atmosphere, to prevent copper and lanthanum from being oxidized to form oxides.
[0046] The present invention also provides an electrode for synthesizing RT base prepared by the above preparation method.
[0047] The present invention also provides a method for synthesizing RT base, comprising: using the electrode or the electrode prepared by the preparation method, taking 4-nitrodiphenylamine as a reaction substrate, and obtaining RT base after electrochemical reaction.
[0048] Furthermore, the parameters of the electrochemical reaction are: temperature of 20 to 60° C.; and / or current of 5 to 100 mA; and / or voltage of 1.8 to 6 V; and / or time of 8 to 12 h; and / or,
[0049] The concentration of 4-nitrodiphenylamine in the electrolyte is 10 to 80 mmol / L, preferably 40 to 60 mmol / L; and / or,
[0050] When the electrochemical reaction is performed, the electrolyte includes an acidic compound; preferably, the acidic compound includes at least one of sulfuric acid and a sulfonic acid compound; more preferably, the sulfonic acid compound includes at least one of methanesulfonic acid and trifluoromethanesulfonic acid; and / or,
[0051] The concentration of the electrolyte in the electrolyte solution is 0.1 to 1 mol / L.
[0052] The technical solution of the present invention has the following advantages:
[0053] 1. The electrode for synthesizing RT base provided by the present invention comprises a substrate and an active component loaded on the surface of one side of the substrate, wherein the active component comprises copper and lanthanum. The electrode of the present invention is a solid polymer (SPE) electrode, and the active components copper and lanthanum are loaded on the surface of the substrate, so that the catalyst is arranged at zero spacing on the electrode, which greatly reduces the power consumption. The active component copper has high selectivity, and lanthanum can improve the catalytic activity and the durability and life of the electrode. The electrode is used to synthesize RT base, and the electrode has high reduction activity and strong stability in use, and can maintain efficient and stable performance during long-term electrolysis. In addition, the electrode of the present invention can also improve the conversion rate, product selectivity and Faraday efficiency of raw materials for synthesizing RT base, synthesize target compounds more efficiently, improve production efficiency, and avoid the use of precious metal catalysts, which is convenient to operate, has low equipment requirements, and is suitable for large-scale production. Compared with the existing nickel catalyst, the copper and lanthanum compound of the present invention are used, and the RT base is prepared by electrochemical reaction. The electrode has high electrocatalytic activity and long service life, avoiding the defects of low reduction activity, easy collapse of structure, and short life of nickel catalyst.
[0054] 2. The method for synthesizing RT base provided by the present invention uses the electrode provided by the present invention to synthesize RT base. The electrochemical reaction process has low temperature and low voltage, mild electrolysis conditions, low energy consumption, few by-products, and is environmentally friendly. DETAILED DESCRIPTION
[0055] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0057] 4-Nitrodiphenylamine: Aladdin reagent, industrial product, >99.0% (HPLC); sulfuric acid: Xilong Chemical, industrial product, >98.0%; polyethylene glycol: Aladdin, molecular weight about 2000; sodium borohydride: Aladdin; potassium borohydride: Aladdin; lithium aluminum hydride: Aladdin; lanthanum carbonate: Aladdin; lanthanum phosphate: Aladdin; lanthanum chloride: Aladdin; lanthanum fluoride: Aladdin; Nafion117 solution: purchased from DuPont Chemours, purity AR, Nafion resin in the solution is about 5%; hydroxyethyl cellulose: Aladdin; glycerol: Aladdin; hydroxymethyl cellulose: Aladdin. Platinum nanoparticles: Scientific Materials Station, research grade.
[0058] Example 1
[0059] This embodiment provides a method for preparing a catalyst for synthesizing RT base, comprising the following steps:
[0060] Copper sulfate was weighed and placed in a 100 mL reaction kettle, polyethylene glycol was added, and an ethylene glycol solution of sodium borohydride (the concentration of the sodium borohydride solution was 0.2 mol / L) was slowly added, and the nano-copper suspension was obtained after reacting at 180°C for 3 hours. Among them, the molar ratio of copper sulfate to sodium borohydride was 1:1.5, and the molar ratio of polyethylene glycol to copper sulfate was 30:1.
[0061] Carboxymethyl cellulose, Nafion 117 solution and lanthanum carbonate are added to the nano-copper suspension and mixed to obtain a slurry; wherein the mass ratio of copper element in copper sulfate, carboxymethyl cellulose and Nafion 117 is 100:8:6, and the mass ratio of copper in copper sulfate to lanthanum in lanthanum carbonate is 80:1.
[0062] At 160°C and in a nitrogen atmosphere, the slurry was sprayed evenly on the cathode side of the perfluorosulfonic acid membrane using a spray gun, with a spraying speed of 0.1 m / s and a spraying distance of 0.2 cm; the other side of the perfluorosulfonic acid membrane was coated with a platinum nanoparticle coating (a LUXORPt nano-spray platinum instrument was used to spray platinum nanoparticles on one side of the perfluorosulfonic acid membrane to form a coating with a thickness of 50 nm), which was the anode side. In a nitrogen atmosphere, the perfluorosulfonic acid membrane was heated to 360°C and kept warm for 2 hours to obtain an SPE electrode with an electrode size of 1 cm×1 cm. The total loading of copper and lanthanum on the perfluorosulfonic acid membrane was 6 mg / cm 2 .
[0063] This embodiment also provides a method for synthesizing RT base, comprising:
[0064] The above-mentioned SPE electrode is used as an electrode in an H-type electrolytic cell, 4-nitrodiphenylamine is used as a reaction substrate, and the electrolyte in the electrolyte includes sulfuric acid; the concentration of sulfuric acid in the electrolyte is 0.5 mol / L, and the concentration of 4-nitrodiphenylamine is 50 mmol / L. The reaction is carried out at a temperature of 20°C, a voltage of 2.2V, and a current of 10mA for 8 hours, and RT base is obtained after extraction, filtration, and drying.
[0065] Example 2
[0066] This embodiment provides a method for preparing a catalyst for synthesizing RT base, comprising the following steps:
[0067] Weigh copper carbonate and place it in a reaction kettle, add glycerol, slowly add an aqueous solution of potassium borohydride (the concentration of the potassium borohydride solution is 0.4 mol / L), and react at 220°C for 7 hours to obtain a nano copper suspension, wherein the molar ratio of copper carbonate to potassium borohydride is 1:3.5, and the molar ratio of glycerol to copper carbonate is 40:1.
[0068] Carbomer, Nafion 117 solution and lanthanum phosphate are added to the nano copper suspension and mixed to obtain a slurry; wherein the mass ratio of copper element in copper carbonate, carbomer and Nafion 117 is 100:6:9, and the mass ratio of copper in copper carbonate to lanthanum in lanthanum phosphate is 50:1.
[0069] At 170°C and in a nitrogen atmosphere, the above slurry was uniformly sprayed on the cathode side of the perfluorosulfonic acid membrane using a spray gun, with a spraying speed of 0.6 m / s and a spraying distance of 1 cm; wherein the other side of the perfluorosulfonic acid membrane was coated with a platinum nanoparticle coating (same as in Example 1), which was the anode side. In a nitrogen atmosphere, the perfluorosulfonic acid membrane was heated to 380°C and kept warm for 3 hours to obtain an SPE electrode with an electrode size of 20 cm×20 cm. The total loading of copper and lanthanum on the perfluorosulfonic acid membrane was 7 mg / cm 2 .
[0070] This embodiment also provides a method for synthesizing RT base, comprising:
[0071] The above-mentioned SPE electrode is used as an electrode in an H-type electrolytic cell, 4-nitrodiphenylamine is used as a reaction substrate, and the electrolyte in the electrolyte includes sulfuric acid; the concentration of sulfuric acid in the electrolyte is 0.7 mol / L, and the concentration of 4-nitrodiphenylamine is 20 mmol / L. The reaction is carried out at a temperature of 50°C, a voltage of 5.3V, and a current of 5mA for 11 hours, and RT base is obtained after extraction, filtration, and drying.
[0072] Example 3
[0073] This embodiment provides a method for preparing a catalyst for synthesizing RT base, comprising the following steps:
[0074] Weigh copper chloride and place it in a reaction kettle, add diethylene glycol, slowly add lithium aluminum hydride tetrahydrofuran solution (the concentration of lithium aluminum hydride solution is 0.5 mol / L), and react at 200°C for 6 hours to obtain a nano copper suspension. The molar ratio of copper chloride to sodium borohydride is 1:0.5, and the molar ratio of diethylene glycol to copper chloride is 100:1.
[0075] Hydroxyethyl cellulose, Nafion 117 solution and lanthanum chloride are added to the nano copper suspension and mixed to obtain a slurry; wherein the mass ratio of copper element in copper chloride, hydroxyethyl cellulose and Nafion 117 is 100:5:8, and the mass ratio of copper in copper chloride to lanthanum in lanthanum chloride is 100:1.
[0076] At 165°C and in a nitrogen atmosphere, the above slurry was uniformly sprayed on the cathode side of the perfluorosulfonic acid membrane using a spray gun, with a spraying speed of 0.8 m / s and a spraying distance of 0.6 cm; wherein the other side of the perfluorosulfonic acid membrane was coated with a platinum nanoparticle coating (same as in Example 1), which was the anode side. In a nitrogen atmosphere, the perfluorosulfonic acid membrane was heated to 390°C and kept warm for 5 hours to obtain an SPE electrode with an electrode size of 100 cm×100 cm. The total loading of copper and lanthanum on the perfluorosulfonic acid membrane was 6 mg / cm 2 .
[0077] This embodiment also provides a method for synthesizing RT base, comprising:
[0078] The above-mentioned SPE electrode is used as an electrode in an H-type electrolytic cell, 4-nitrodiphenylamine is used as a reaction substrate, and the electrolyte in the electrolyte includes sulfuric acid; the concentration of sulfuric acid in the electrolyte is 1 mol / L, and the concentration of 4-nitrodiphenylamine is 80 mmol / L. The reaction is carried out at a temperature of 40°C, a voltage of 4.7V, and a current of 30mA for 10 hours, and RT base is obtained after extraction, filtration, and drying.
[0079] Example 4
[0080] This embodiment provides a method for preparing a catalyst for synthesizing RT base, comprising the following steps:
[0081] Weigh copper chloride and place it in a reaction kettle, add polyethylene glycol, slowly add ethylene glycol solution of sodium borohydride (the concentration of sodium borohydride solution is 0.2 mol / L, and react at 240°C for 8 hours to obtain a nano copper suspension. Among them, the molar ratio of copper chloride to sodium borohydride is 1:4, and the molar ratio of polyethylene glycol to copper chloride is 70:1.
[0082] Carboxymethyl cellulose, Nafion 117 solution and lanthanum fluoride are added to the nano-copper suspension and mixed to obtain a slurry; wherein the mass ratio of copper element in cupric chloride, carboxymethyl cellulose and Nafion 117 is 100:6:10, and the mass ratio of copper in cupric chloride to lanthanum in lanthanum fluoride is 50:1.
[0083] At 180°C and in a nitrogen atmosphere, the above slurry was uniformly sprayed on the cathode side of the perfluorosulfonic acid membrane using a spray gun, with a spraying speed of 1 m / s and a spraying distance of 0.8 cm; wherein the other side of the perfluorosulfonic acid membrane was coated with a platinum nanoparticle coating (same as in Example 1), which was the anode side. In a nitrogen atmosphere, the perfluorosulfonic acid membrane was heated to 400°C and kept warm for 4 hours to obtain an SPE electrode with an electrode size of 40 cm×40 cm. The total loading of copper and lanthanum on the perfluorosulfonic acid membrane was 8 mg / cm 2 .
[0084] This embodiment also provides a method for synthesizing RT base, comprising:
[0085] The above-mentioned SPE electrode is used as an electrode in an H-type electrolytic cell, 4-nitrodiphenylamine is used as a reaction substrate, and the electrolyte in the electrolyte includes sulfuric acid; the concentration of sulfuric acid in the electrolyte is 0.8 mol / L, and the concentration of 4-nitrodiphenylamine is 20 mmol / L. The reaction is carried out at a temperature of 50°C, a voltage of 6V, and a current of 100mA for 12 hours, and RT base is obtained after extraction, filtration, and drying.
[0086] Comparative Example 1
[0087] This comparative example provides a catalyst. Compared with Example 1, copper sulfate is replaced with nickel sulfate during the preparation of the catalyst to prepare a SPE electrode modified with skeleton nickel and lanthanum. The RT base synthesis process is the same as that of Example 1.
[0088] Comparative Example 2
[0089] This comparative example provides a catalyst. Compared with Example 1, no lanthanum source is added during the preparation of the catalyst, and the RT base synthesis process is the same as that of Example 1.
[0090] Test Example 1
[0091] This test example provides performance tests of various embodiments and comparative examples, including:
[0092] RT base yield: The yield of RT base was determined by liquid chromatography, and the yield of RT base was used to characterize the electrode catalytic activity. The parameters of the liquid chromatography method were: Agilent liquid chromatography 1260, chromatographic column: Zorbax ODS 250 mm × 4.6 mm (inner diameter) stainless steel column; mobile phase: methanol, acetonitrile and water in a volume ratio of 0.4:0.4:0.2; flow rate: 0.8 ml / min; UV detection wavelength: 285 nm; injection volume: 10 μl.
[0093] Current efficiency: calculated using Faraday's second law.
[0094] Electrode service life: Verify according to the conditions of each embodiment and record the operating time when the current efficiency is lower than 70%, that is, the service life of the electrode.
[0095] Table 1 Test results
[0096] Example Yield of RT Base Current efficiency Lifespan / h Example 1 98% 99% 3500 Example 2 95% 93% 2800 Example 3 96% 92% 2000 Example 4 92% 92% 1500 Comparative Example 1 76% 56% 800 Comparative Example 2 51% 43% 1000
[0097] It can be seen from the above results that the electrode of the present invention has a higher yield and current efficiency when used in synthesizing RT base, and the electrode has a longer service life.
[0098] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. An electrode for synthesizing RT base, characterized in that: The invention comprises a substrate and active components loaded on a surface of one side of the substrate, wherein the active components comprise copper and lanthanum.
2. The electrode according to claim 1, characterized in that The mass ratio of copper to lanthanum is (50-100):
1.
3. The electrode according to claim 1 or 2, characterized in that The substrate comprises an ion exchange membrane; preferably, the ion exchange membrane comprises a perfluorosulfonic acid ion exchange membrane; and / or, The surface of the substrate on the side opposite to the active component is loaded with an anode active material; and / or, The loading amount of the active component in the matrix is 5-10 mg / cm 2 and / or, The size of the electrode is 1×1 cm 2 ~100×100cm 2 ; Preferably, the size of the electrode is 20×20 cm 2 ~50×50cm 2 .
4. A method for preparing an electrode for synthesizing RT base, characterized in that: include: (1) preparing a copper-containing suspension; (2) adding a lanthanum source to the copper-containing suspension to prepare a slurry containing copper and lanthanum; (3) The slurry is coated on one surface of the substrate and sintered.
5. The preparation method according to claim 4, characterized in that: The step (1) is to prepare a copper salt solution from a copper salt; and to add a reducing agent to the copper salt solution to react and prepare the copper-containing suspension; Preferably, the copper salt includes at least one of a monovalent copper salt and a divalent copper salt; Preferably, the molar ratio of the copper salt to the reducing agent is 1:(0.5-4); Preferably, the reaction temperature is 120-240°C and the reaction time is 3-8h; Preferably, the copper-containing suspension is a nano-copper suspension; Preferably, the reducing agent comprises at least one of alkali metal borohydrides; Preferably, the alkali metal borohydride comprises at least one of sodium borohydride and potassium borohydride; Preferably, before carrying out the reaction, the method further comprises the step of adding an alcohol organic substance; Preferably, the alcohol organic compound contains at least 2 hydroxyl groups; Preferably, the alcohol organic matter includes at least one of an alcohol polymer and an alcohol compound; Preferably, the number of carbon atoms in the alcohol compound is 2 to 7; Preferably, the alcohol polymer comprises polyethylene glycol; Preferably, the alcohol compound includes at least one of diethylene glycol and glycerol.
6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the lanthanum source includes at least one of lanthanum fluoride, lanthanum oxide, lanthanum nitride, lanthanum carbide, lanthanum phosphide, lanthanum nitrate, lanthanum phosphate, lanthanum carbonate and lanthanum sulfate; Preferably, the slurry further comprises perfluorosulfonic acid resin; Preferably, the mass ratio of the copper element in the copper salt to the perfluorosulfonic acid resin is 100:(5-10); Preferably, the slurry further comprises a pore former; Preferably, the mass ratio of the copper element in the copper salt to the pore-forming agent is 100:(5-10); Preferably, the pore-forming agent comprises at least one of acrylic cross-linked resin and cellulose and its derivatives; Preferably, the acrylic acid cross-linked resin comprises carbomer; Preferably, the cellulose includes at least one of carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, ethyl cellulose and hydroxyethyl methyl cellulose.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The step (3) is to apply the coating by spraying; Preferably, the spraying parameters include: a temperature of 160 to 180° C.; and / or a spraying speed of 0.1 to 1 m / s; and / or a spraying distance of 0.1 to 1 cm; Preferably, the spraying is carried out under a protective atmosphere; Preferably, the sintering temperature is 350-400°C; Preferably, the sintering is performed under a protective atmosphere.
8. An electrode for synthesizing RT base obtained by the preparation method according to any one of claims 4 to 7.
9. A method for synthesizing RT base, characterized in that: include: The electrode according to any one of claims 1 to 3 or the electrode prepared by the preparation method according to any one of claims 4 to 7 is used, and 4-nitrodiphenylamine is used as a reaction substrate to obtain RT base after electrochemical reaction.
10. The method according to claim 9, characterized in that The parameters of the electrochemical reaction are: temperature of 20-60° C.; and / or current of 5-100 mA; and / or voltage of 1.8-6 V; and / or time of 8-12 h; and / or, The concentration of 4-nitrodiphenylamine in the electrolyte is 10 to 80 mmol / L, preferably 40 to 60 mmol / L; and / or, When the electrochemical reaction is performed, the electrolyte includes an acidic compound; preferably, the acidic compound includes at least one of sulfuric acid and a sulfonic acid compound; more preferably, the sulfonic acid compound includes at least one of methanesulfonic acid and trifluoromethanesulfonic acid; and / or, The concentration of the electrolyte in the electrolyte solution is 0.1 to 1 mol / L.